Antioxidant, cytotoxic activities, and structure-activity relationship of gallic acid-based indole derivatives - Khaledi, H.; Alhadi, A.A.; Yehye, W.A.; Ali, Hapipah Mohd; Abdulla, Mahmood Ameen; Hassandarvish, P. (Wiley-VCH Verlag, 2011)
A new series of gallic hydrazones containing an indole moiety was synthesized through the reaction of gallic hydrazide and different indole carboxaldehydes. Their antioxidant activities were determined on DPPH radical scavenging and inhibition of lipid peroxidation. The in-vitro cytotoxic activities of the compounds were evaluated against HCT-116 (human colon cancer cell line) and MCF-7 (estrogen-dependent human breast cancer cell line) by the MTT method. An attempt to correlate the biological results with their structural characteristics has been done. A limited positive structure activity relationship was found between cytotoxic and antioxidant activities.